IMPLEMENTASI PROGRAM BANTUAN SOSIAL DINAS SOSIAL DAERAH ISTIMEWA YOGYAKARTA BAGI LANJUT USIA - Yuniasih, Nurul; Supardal, Supardal (Journal of Indonesian Rural and Regional Government, 2025)
The Regional Government of the Special Region of Yogyakarta (DIY), through the Social Service Office, implements the Social Security Program for the Elderly as part of the Governor’s policy to address poverty, with a specific focus on reducing extreme poverty. The policy on Social Assistance for the Elderly is regulated under Regional Regulation No. 30 of 2024, which amends Regional Regulation No. 22 of 2021 concerning the Procedures for Grants and Social Assistance. The implementation of this policy involves several regional agencies, including Bapperida DIY, BPKA DIY, the Legal Bureau of the Regional Secretariat, the DIY Inspectorate, and the Social Service Office, each playing roles according to their respective duties and functions. The Social Service Office is directly responsible for poverty alleviation, making it the primary institution in distributing social assistance. This study aims to examine how the Social Assistance Program for the Elderly is distributed by the Social Service Office of DIY. A participatory descriptive qualitative research method was employed, allowing the researcher to gain in-depth understanding of the implementation of the policy. The findings show that the Social Service Office has made maximum efforts in terms of accountability, transparency, compliance with regulations, and accuracy of beneficiary data. In 2024, the distribution showed increased absorption, indicating effective policy implementation. Furthermore, the use of the VA Dashboard System to monitor social assistance distribution demonstrates the success of the Social Service Office in fostering cross-agency communication, optimizing resources with clear roles, and strengthening inter-bureaucratic commitment, policy coordination, and oversight